Abnormal Expression of DICER1 Leads to Dysregulation of Inflammatory Effectors in Human Synoviocytes. (28th May 2019) - Jiang, Congshan; Xu, Jing; Zhu, Wenhua; Cai, Yongsong; Wang, Si; Guo, Yuanxu; Xu, Ke; Geng, Manman; Hussain, Nazim; Han, Yan; Zhang, Fujun; Ning, Qilan; et al.
Abstract : Dysregulation of multiple microRNAs widely takes place during rheumatoid arthritis (RA) and experimental arthritides. This study is performed to explore the possible mechanism underlying DICER1 deficiency-mediated inflammation in human synoviocytes SW982. Firstly, RNAi of DICER1 led to increased COX2, MMP3, and MMP13 protein production, while DICER1 overexpression could reduce MMP13 expression. Secondly, the increase of IL-8 and decrease of TGF- β 1 and TIMP1 were determined in the supernatant derived from DICER1 siRNA-treated cells, while DICER1 overexpression was found capable to reverse this effect. Ingenuity pathway analysis (IPA) software predicted that the Dicer1 deficiency-induced dysregulated cytokines in synoviocytes could possibly lead to the inflammatory disorders in the synovial tissue. Moreover, DICER1 deficiency could also reduce apoptosis, while DICER1 overexpression was found to decrease the proliferation and enhance apoptosis. In addition, DICER1 deficiency could lower the expression of multiple RA-related miRNAs such as miR-155. Meanwhile, DICER1 overexpression could rescue their low expression levels. And then, gain or loss of miR-155 function could regulate the protein levels of MMP3 and MMP13. These results indicated that DICER1 might play its role through regulating its downstream RA-related miRNAs. Our data demonstrated that DICER1 deficiency could cause multiple proinflammatory events in human synoviocytes SW982. This mechanism study might provide the possible target molecule to modify the inflammatory destruction and overproliferation in synoviocytes.